Discrete simulation application for developing improvements for the processes of the emergency service department of a public hospital - Delgado Encinas, Karem (2011)
In this investigation it has been evaluated the current situation of the emergency area that assists adults, in a public hospital of Peru. The software Arena was used to perform discreet simulations, with the objective of obtaining improvement proposals that allow reduce the total time of the patient’s permanency in this area before he is to discharge from hospital or admitted in the hospital. A simulation model was developed where several types of patients were identified that were assisted in the surgery, medicine, and traumatología topics. In some cases clinical analysis was required. For reduce the time of a patient’s permanency in the system diverse possibilities were evaluated, being the best alternative a modification in the schedule of the doctors’ attention in the medicine topic. This solution considers that four doctors assist from 7:00 a.m. to 7:00 p.m. and two doctors from 7:00 p.m. to 7:00 a.m.